What effect does a structured home-based exercise programme have on people with Huntington’s disease? A randomized, controlled pilot study - Khalil, Hanan; Quinn, Lori; van Deursen, Robert; Dawes, Helen; Playle, Rebecca; Rosser, Anne; Busse, Monica (Clinical rehabilitation, 2013)
Objective: The aim of this study was to explore feasibility, safety and outcome of an exercise intervention in people with Huntington’s disease. Design: A randomized controlled pilot trial. Setting: A home-based exercise programme. Subjects: A total of 25 subjects with early to mid-stage Huntington’s disease. Intervention: Subjects were randomly allocated to either an exercise intervention (n = 13) or a control group (n = 12). Subjects in the exercise intervention group were asked to perform exercises at home three times a week for eight weeks using an exercise DVD, specifically developed for this purpose. The control group received their usual care. Measures: Adherence in the intervention group was calculated from exercise diaries. Measures of gait, balance, function, level of physical activity and quality of life were evaluated. Analysis of covariance was used to compare follow-up scores across groups after adjustment for chance baseline differences. Effect sizes were calculated. Results: Eleven participants from the intervention and ten from the control group completed the study. Mean adherence was 29.4 SD 1.8 for the 32 prescribed sessions. There were no related adverse events. Differences between groups were observed in gait speed, balance, function and level of physical activity, but not quality of life as measured by the SF36. Effect sizes were large (>0.8) for the majority of the outcomes. Conclusions: Short-term structured home exercise programmes are feasible, beneficial and safe for people with early to mid-stage of Huntington’s disease. Our findings support the implementation of a larger trial of longer-term home exercise.